ANTIBACTERIAL ACTIVITY OF APRICOT KERNEL EXTRACT CONTAINING AMYGDALIN - Al-Bakri, Salih; Nima, Zeid; Jabri, Raya; Ajeel, Esra’a (Iraqi Journal of Science, 2024)
Amygdalin was extracted from apricot kernels, the chemical characteristics of amygdalin are: white, crystalline, and inodorous powder, slightly soluble in cold water, very soluble in hot water, alcohol and acetone, and insoluble in ether. It has a pH of 7 in saturated aqueous solution. Amygdalin purity in the extract was estimated to give 99.5%. Amygdalin was identified in the extract by FT-IR.The sensitivity of some species of pathogenic bacteria included Pseudomonas aeruginosa, Serratia marcescens, Staphylococcus aureus, and Streptococcus pyogenes to different concentration of amygdalin (2%, 4%, 6%, 8%, and 10%) was tested to find out the role of amygdalin as antibacterial agent.The experimental results of bacterial sensitivity to different concentrations of amygdalin, showed sensitivity of tested bacteria to all concentrations of amygdalin except concentration 2% amygdalin, bacterial species were resistant to it.